Saudi-Indo Digital Financial Literacy: Empowering PCIM Saudi Arabia Students Through Simple Financial Management Training and Sharia Based Investment - Sahabuddin Nanda; M. Yusuf K; A. Ifayani Haanurat; Sukmawati Sukmawati; Muchriana Muchran; Wa Ode Rayyani; Asri Jaya; Zalkha Soraya; Samsul Bahari; Muhammad Umar A (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This community service activity aims to improve students' financial literacy at the Special Branch of Muhammadiyah (PCIM) in Saudi Arabia through training in basic financial management and sharia-based investment. The program was held at the PCIM Saudi Arabia Centre (Rumah Buya Hamka), Medina, on November 11, 2025, and involved collaboration among three universities: Muhammadiyah University Makassar, Muhammadiyah University Buton, and Alkhairaat University. The methodological approach used was participatory-educational with interactive lectures, discussions, simulations, and hands-on practice. The activity results showed a significant increase in participants' conceptual understanding and practical skills in budgeting, cash flow management, financial planning, and recognising safe and productive sharia-compliant investment instruments. In addition, this activity strengthened students' ethical awareness and financial responsibility by integrating Islamic values into each training session. This program contributes to strengthening the economic capacity of diaspora students and strengthening collaborative networks across universities and the Muhammadiyah community in Saudi Arabia. Thus, this activity has the potential to serve as a model for community service grounded in adaptive, applicable, and sustainable Islamic financial literacy, relevant for replication among Indonesian student communities in various countries. Contribution to Sustainable Development Goals (SDGs):SDG 4: Quality EducationSDG 8: Decent Work and Economic GrowthSDG 10: Reduced InequalitiesSDG 12: Responsible Consumption and Production